Evaluation of Covid-19 vaccination in 2021 in nganjuk regency - Mariyah, Mariyah; Satibi, Satibi; Iswandi, Iswandi (Science Midwifery, 2024)
Corona Virus Disease 2019 (COVID-19) is an infectious disease that has never been identified before in humans, in severe cases it can cause pneumonia, acute respiratory syndrome, kidney failure, and even death which has been declared a non-natural disaster as a public health emergency. The purpose of this study is to determine and evaluate the implementation of COVID-19 vaccination which includes planning needs, distribution, storage, recording and reporting, monitoring and overcoming adverse events after COVID-19 vaccination, and monitoring evaluation in accordance with the Minister of Health Regulation Number HK.01.07 / MENKES / 4638 / 2019. This research method uses observational research with a descriptive approach. This research is conducted to assess a program that is being or has been implemented. The results of this research are used to improve and/or refine the program or system. In managing the results of this evaluation research, simple statistical analysis is usually used. The implementation of COVID-19 vaccination in Nganjuk Regency includes planning needs, distribution, storage, recording and reporting, monitoring and overcoming adverse events after COVID-19 vaccination, as well as monitoring and evaluation in accordance with Minister of Health Regulation Number HK.01.07/MENKES/4638/2021. The evaluation of the implementation of COVID-19 vaccination in 2021 in Nganjuk District includes several components, namely planning, organizing, mobilizing, monitoring, and output. However, at the planning stage, the need for COVID-19 vaccination stocks is not in accordance with the achievement target. The distribution and storage of SOPs have been carried out well, SOPs are carried out with references in accordance with their respective technical instructions along with recording AEFI reporting and monitoring.